Measuring The Law On The Formation Of Laws And Regulations As A Touchstone Constitutional Review - Djalil, Mochamad; Kumalasari, Dewi Ratih (PT. Anagata Sembagi Education, 2025)
This study examines the constitutional supremacy in shaping statutory regulations, positioning it both as a guiding framework and a binding compliance standard for the public particularly state authorities and their institutions. It argues that the Law on the Formation of Laws and Regulations serves as a definitive and legitimate benchmark in constitutional review. Nonetheless, practical realities reveal instances where the principle of utility can override arguments concerning formal defects in legislation and Government Regulations in Lieu of Law (Perppu). Employing a normative legal research method that integrates statutory and conceptual approaches, this paper provides a descriptive analysis of the issue. The findings indicate that constitutional review functions as an embodiment of constitutional supremacy through the judicial examination of laws, with the Law on the Formation of Laws and Regulations serving as a key parameter in determining constitutionality a parameter whose application continues to evolve.